Coastal engineering theory and practice - Sundar, V. (Vallam); Sannasiraj, S. A. (Advanced series on ocean engineering, 2019)
This book can potentially serve as a comprehensive textbook for students pursuing this subject either as degree or an elective course. It covers all the fundamental physics behind the different phenomena taking place in the near shore regions and the coast as well as the various methods to estimate its impact. Basic knowledge of water wave mechanics is crucial in understanding the coastal processes taking place in the near shore. The assessment of incident forces due to wind, wave, tide, current etc. is important to evaluate the resultant impact they cause on the shoreline and structures.This book emphasizes the importance of sediment dynamics by analyzing the sediment characteristics, the physics of its motion and movement, factors responsible for the fate of sediments etc. It also highlights the erosion problem which is most prevalent across the sandy coasts, additionally erosion combating methods and techniques are also described with real time field problems and their solutions.A wide range of coastal structures and their design principles are included in this book in order to give the reader a holistic understanding to the readers. This book also includes the design challenges and introduces the reliable modeling tools and techniques, which is very useful for beginners working in this discipline